Do investors differentiate the dimensions of an analyst's credibility? An examination of bold valence, reputation and accuracy on investors’ competence and trustworthiness judgements - Li, Xiao (2015)
Identifying the determinants of analysts’ credibility (composed of competence and trustworthiness) is an important issue because it affects both analysts’ career prospects and investors’ investment choice making. In a bold forecast setting, I experimentally examine whether and how an analyst characteristic, reputation, and two forecast features, forecast accuracy and bold valence (i.e., whether the bold forecast is positively bold or negatively bold relative to the consensus forecast), jointly influence the two dimensions of analyst credibility. I find that, in the absence of accuracy information, investors trust analysts more when they make a negatively (as opposed to positively) bold forecast, with the effect evident only for lower reputation analysts. Upon revelation of accuracy information, lower (as compared to higher) reputation analysts who issue a negatively bold forecast gain more competence increases when the forecast is accurate, and do not suffer greater competence losses when the forecast is inaccurate. For the trustworthiness dimension, although lower reputation analysts do not experience greater trustworthiness increases than higher reputation analysts for a negatively bold and accurate forecast, their post-accuracy trustworthiness is advanced to a level comparable to that of a higher reputation analyst. Overall, my study contributes to the literature by introducing a new forecast attribute, bold valence. In addition, I am the first to show that the two dimensions of analyst credibility, competence and trustworthiness, are differentially influenced by different analyst and forecast attributes. My study also has implications for analysts by identifying ways they can build credibility with investors.